W sprawie przełomu pozytywistycznego. Spory krytyczne wokół Zarysu literatury polskiej z ostatnich lat szesnastu Piotra Chmielowskiego - Budrewicz, Tadeusz; Sobieraj, Tomasz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2015)
The 5th volume of the series Polemika Krytycznoliteracka w Polsce (“Critical Literary Argument in Poland”) deals with the nationwide critical dispute over the famous study by Piotr Chmielowski entitled Zarys literatury polskiej z ostatnich lat szesnastu, which was published in 1881. Its author, one of the most prominent Polish positivist literary critics, focused on the so-called positivistic turn that occurred after the collapse of the January Uprising in 1864. Chmielowski’s thesis caused a lot of controversy among literary critics and publicists. The author was accused of a bias against ideological opponents. The sharp dispute included many authors: some belonged to the liberal and positivistic group, whereas others represented conservative views. The former group included Aleksander Świętochowski, Józef Kotarbiński, Antoni Gustaw Bem, Teodor Tomasz Jeż; among the latter there were Adam Goraj, Ludwik Dębicki, Kazimierz Waliszewski. The dispute over Chmielowski’s book was crucial for the history of Polish literature in the second half of the 19th century. It also contributed to ideological and political discussion among the Polish intelligentsia.
About the positivism breakthrough. Critical disputes over Piotr Chmielowski’s Zarys literatury polskiej z ostatnich lat szesnastu
Keywords: Piotr Chmielowski; Adam Goraj; Józef Kotarbiński; Adam Brzoza; Antoni Gustaw Bem; Aleksander Świętochowski; Ludwik Dębicki; Karol Waliszewski; Polemika Krytycznoliteracka w Polsce